Grace stirs it up - Casanova, Mary (Girl of the year. Grace, 2015)
Inspired by her grandparents' bakery and her recent visit to Paris, nine-year-old Grace leads her friends in starting La Petite Patisserie, making and selling French pastries at school and special events, but they soon discover that starting a new business is not always easy--or fun.